Study On The Distribution Of Pongamia Pinnata Trees In The Coastal Forest Of Hatusua Village, Kairatu Subdistrict, West Seram Regency - Demianus Tamala; Irwanto Irwanto; Yulianus Dominggus Komul (Jurnal Sylva Scienteae, 2024)
Study on the Distribution of Pongamia Pinnata (Pongamia Pinnata) Wood Species on the Coastal Forest of Hatusua Village, Kairatu Subdistrict, West Seram Regency. The research objective is to determine the morphology and distribution pattern of Pongamia Pinnata wood, using data collection methods such as purposive sampling surveys, a combination of transect and quadrat line methods conducted along the observation paths on the coastal forest. The results of the study show that morphologically, Pongamia Pinnata wood is a tree with woody stems, grayish in color, round in shape with rough and protruding stem surfaces. The height of this tree ranges from 8 to 37.5 meters with a stem diameter reaching 84 cm. The vegetation species diversity for seedling level = H’=2.79, Sapling = 3.46, and tree level H’ =3.17, which is classified as experiencing moderate to high diversity with a clustered distribution pattern